Pengembangan Pariwisata Berkelanjutan melalui Local Wisdom: Desa Wisata Penglipuran - Ida Ayu Made Adi Pradnya Putri; Adi Putra Suwecawangsa (Wacana: Jurnal Ilmu Sosial dan Ilmu Politik Interdisiplin, 2025)
This research aims to provide an analysis related to the local wisdom of a community, especially in Penglipuran Tourism Village that can affect the development of sustainable tourism of a tourist attraction. This research uses qualitative methods with descriptive research design through literature study. The management of tourist attractions in Penglipuran Village combines environmental and cultural sustainability through policies such as the prohibition of the use of motorized vehicles and integrated waste management. In addition, Penglipuran has maintained the beautiful environment and the quality of life of their people. Tri Hita Karana is the guideline of life or values that are held firmly by the Penglipuran Village community in living their daily lives. All aspects of their lives are very relevant to their local wisdom, including the tourism sector. Through the local wisdom held firmly by the local community, this village has successfully applied their values in developing sustainable tourism, which in turn has become the hallmark or tourist attraction of Penglipuran Village for tourists, both local and tourism.